Utility of Geriatric Assessment Tools in the Management of Breast Cancers - Pavan Deepak Mandigala Venkata Ramana; Gulafshan Jabi (Journal of Radiation and Cancer Research)
Breast cancer is a common malignancy in older women, and the incidence of breast cancer increases with age. Management of breast cancer in the elderly is challenging given the presence of comorbidities and declining functional status. Geriatric assessment (GA) is a multidimensional evaluation tool that assesses the functional, cognitive, social, and psychological aspects of older adults. The aim of this literature review is to explore the use of GAs in guiding breast cancer treatment decisions for older patients. The review focuses on the evidence supporting the use of GA in identifying older adults at risk of adverse outcomes from cancer treatment and guiding treatment decision-making. The review also discusses the challenges and limitations of these novel metrics and provides recommendations for future research. The aim of this review is to iterate the importance of GA tools in guiding the practices of geriatric breast cancer in India.